OP75 Sugar Sweetened Beverages Coverage in the British Media – An Analysis of Public Health Advocacy versus Pro-Industry Messaging. (13th September 2016) - Elliott-Green, A; Hyseni, L; Lloyd-Williams, F; Bromley, H; Capewell, S
Abstract : Background: Sugar–sweetened beverages (SSBs) are an increasing contributor to rising rates of diabetes, obesity and cardiovascular disease. The media has an important role in framing perceptions of these products and therefore has significant potential to influence public health policy. We assessed the extent of media-based public health advocacy versus pro-industry messaging regarding SSBs. Methods: We conducted a systematic analysis to identify and examine all articles regarding SSBs published in mainstream British print newspapers and their online news websites from 1 st January 2014 to 1 st January 2015. We initially conducted a brief literature search to develop appropriate search terms and categorisations for grouping and analysing the articles. Articles were then coded according to the publishing newspaper, article type, topic, prominence and slant (pro- or anti-SSB). A contextual analysis was undertaken to examine key messages in the articles. Results: 1295 full-text articles published during 2014 were assessed for eligibility of which 374 were included in this analysis. The majority of articles (81%) suggested that SSBs are unhealthy. Messaging from experts, campaign groups and health organisations was fairly consistent about the detrimental effects of SSB on health. SSBs were associated with a large variety of topics and sub-topics, most frequently health effects, followed by regulation and product consumption. Of those articles discussing the health impact of SSBs, the most prominent subtopic was youth's consumption of SSBs. However, relatively few articles assessed any approaches or solutions to potentially combat the problems associated with SSBs. Only a quarter (24%) suggested any policy change. 31% placed the responsibility for combating consumption of sugar on individuals and 36% offered no solutions, merely highlighting the problems associated with SSBs over-consumption. Meanwhile, articles concerning the food industry produced consistent messages emphasising consumer choice and individual responsibility for making choices regarding SSB consumption, and promoting and advertising their products. The food industry thus often managed to avoid association with the negative press that their products were receiving. Conclusion: Sugar–sweetened beverages featured heavily in mainstream British print newspapers and their online news websites during 2014. Public health media advocacy was prominent throughout, with a growing consensus that sugary drinks are bad for people's health. However, the challenge for public health will be to mobilise supportive public opinion to help implement effective regulatory policies. Only then will our population's excess consumption of sugar sweetened beverages come under control.